Symptomatic anaemia 17 years after double valve replacement - Wong, M.H.; Chee, K.H.; Azman, W. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
A 40-year-old Malay woman presented with increasing lethargy, palpitation and shortness of breath, 17 years after a mitral and aortic valve replacement. A Starr-Edwards prosthetic valve replaced the mitral valve, and a Bjork-Shiley prosthetic valve replaced the aortic valve. Biochemical parameters demonstrated intravascular haemolysis, as evidenced by haemoglobin 7.8 g/dL, reticulocyte count 8.4%, lactate dehydrogenase 2,057 IU/L and low haptoglobulin levels (less than 6 mg/dL). Transoesophageal echocardiography revealed a paravalvular leakage over the mitral valve. The haemoglobin levels remained persistently low despite frequent blood transfusions. She successfully underwent a second mitral valve replacement. Her anaemia resolved subsequently.